Toward Green Battery Cells: Perspective on Materials and Technologies (Small Methods 7/2020). Issue 7 (6th July 2020) - Dühnen, Simon; Betz, Johannes; Kolek, Martin; Schmuch, Richard; Winter, Martin; Placke, Tobias
Abstract : The continually increasing consumption of energy and scarce raw materials for the global growth of battery production raises concerns about the carbon footprint and the sustainability of current battery technologies and materials. Article number 2000039 by Simon Dühnen, Martin Winter, an co‐workers, reviews new material approaches, improved production and recycling processes, as well as novel battery chemistries can offer a greener solution for future energy storage devices.